MON-188 The Diagnostic Value of DHEAS in Subtyping Patients with Cushing Syndrome - Liu, Mengsi (J Endocr Soc, 2020)
Objective: Serum dehydroepiandrosterone sulfate (DHEAS) can be used to assess the integrity of the hypothalamic-pituitary-adrenal (HPA) axis. The aim of this study was to evaluate the clinical value of DHEAS in differentiating adrenal Cushing syndrome (ACS) from Cushing’ disease (CD). Methods: We recruited 100 patients with Cushing syndrome, 36 with CD and 64 with ACS. 72 sex-, age- and BMI-matched nonfunctional adrenal adenomas (NFAAs) were served as controls. Clinical and laboratory data were collected. DHEAS levels were measured and DHEAS ratio was calculated by dividing the measured DHEAS by the lower limit of the respective reference range (age- and sex-matched). Results: 1) No significant differences in age, sex, or BMI were detected among the NFAAs, ACS and CD groups. Compared to NFAAs group, ACS patients had lower plasma ACTH levels [1.11(1.11,1.74) vs 5.0 ± 2.9 pmol/L, P<0.01], lower DHEAS levels (24.00 ± 20.72 vs 189.05 ± 82.03 ug/dL, P < 0.01) and lower DHEAS ratio [0.58(0.27,0.98) vs 5.34 ± 3.0]; Plasma ACTH (22.12 ± 14.22 pmol/L), DHEAS (309.4 ± 201.1 ug/dL) and DHEAS ratio (10.51 ± 7.65) in CD patients were significantly higher compared to those in NFAAs and ACS patients (all P<0.01). 2) In ACS patients, there were 53 patients with suppressed ACTH level of <2.0 pmol/L, 11 patients without plasma ACTH suppression (≥2.0pmol/L). Compared to NFAAs, lower DHEAS and DHEAS ratio were detected in these two groups, and no significant differences were found in the DHEAS [15(15, 23.5) vs 23.8 ± 14.4 ug/dL, P=0.86] and DHEAS ratio [0.58(0.27, 0.80) vs 1.0(0.25,2.09) ug/dL, P=0.40] between the two groups. 3) ROC analysis showed that the area under the curve (AUC) of plasma ACTH, serum DHEAS and DHEAS ratio in diagnosing 0.954, 0.997 and 0.990 respectively. The optimal cut-off values for DHEAS and its ratio were 79.1ug/dL, and 2.09, respectively. The diagnostic sensitivity and specificity of plasma ACTH (<2.0pmol/L) were 84.1 and 100%, those of DHEAS were 97.5% and 100%, and those of DHEAS ratio were 95% and 100%, respectively. Conclusions: Patients with different subtype of Cushing syndrome showed distinctive DHEAS levels and DHEAS ratio. DHEAS and DHEAS ratio are useful in differential diagnosis of Cushing syndrome. Especially, when the plasma ACTH level is not conclusive. The measurement of DHEAS may offer a supplementary test to diagnosis ACS from CD. Keywords: Adrenal Cushing syndrome; Cushing disease; Adrenocorticotropic hormone; Dehydroepiandrosterone sulfate